Die Inschriften des Stadtgottesackers in Halle an der Saale (1550-1700) : Quellen zum Bürgertum einer Stadt in der frühen Neuzeit - Krüger, Klaus (2021)
Between 1557 and 1590, the Stadtgottesacker in Halle, a prototype of a Protestant burial ground outside the city walls, was expanded into an architectural unity that in form and completeness has no parallel north of the Alps. The volume contains all the inscriptions prior to 1700 on tombs and on 90 burial vaults, edited and translated in their entirety, along with notes on coats of arms and referenced persons.